2018
DOI: 10.5194/acp-18-13755-2018
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural harvesting emissions of ice-nucleating particles

Abstract: Abstract. Agricultural activities can modify natural ecosystems and change the nature of the aerosols emitted from those landscapes. The harvesting of crops can loft plant fragments and soil dust into the atmosphere that can travel long distances and interact with clouds far from their sources. In this way harvesting may contribute substantially to ice-nucleating particle (INP) concentrations, especially in regions where agriculture makes up a large percentage of land use. However, a full characterization of p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(110 citation statements)
references
References 50 publications
8
98
4
Order By: Relevance
“…This larger variability in the high temperature range has been observed in other studies, too, e.g. for soil or agricultural dust (O'Sullivan et al, 2014;Schiebel, 2017;Suski et al, 2018). One explanation for this behaviour could be that there are multiple INP types in seawater, just like there are in terrestrial samples, leading to a high diversity of the INP spectra at high temperatures.…”
Section: Combined Temperature Regime -Full Ice Nucleation Spectrasupporting
confidence: 66%
“…This larger variability in the high temperature range has been observed in other studies, too, e.g. for soil or agricultural dust (O'Sullivan et al, 2014;Schiebel, 2017;Suski et al, 2018). One explanation for this behaviour could be that there are multiple INP types in seawater, just like there are in terrestrial samples, leading to a high diversity of the INP spectra at high temperatures.…”
Section: Combined Temperature Regime -Full Ice Nucleation Spectrasupporting
confidence: 66%
“…Most notably, from IS data collected on the G-1 and at the Bodega Bay site on 11 February, we observed an increase in n INP at temperatures warmer than −20°C (red points in Figure 8a) to the highest values Filter measurements from the Central Valley on 12 February (not shown) were also very similar to those on 11 February in this region. This increase in n INP at these relatively warmer temperatures is commonly indicative of terrestrial biological INPs (Petters & Wright, 2015;Suski et al, 2018) and back trajectory analysis during this time period (Figure 8b) clearly showed air masses intercepting the terrestrial boundary layer prior to arrival at the Bodega Bay site (red lines). Previous studies have observed an increase in n INP following rain events associated with an increase in such terrestrial biological particle concentrations Prenni et al, 2013;Tobo et al, 2013), suggesting that intense rains have a feedback effect on the production and release of INPs (Morris et al 2019), as observed here.…”
Section: Atmospheric River Eventmentioning
confidence: 76%
“…Figure 2 shows that the hierarchy in ice nucleation activities is similar as observed in the AIDA cloud chamber 210 experiments, with leaf litter and agricultural dust being the most ice-active samples. The steep onset of ice nucleation observed for the agricultural dust at 267 K suggests a contribution from biological particles (Suski et al, 2018). In contrast, the reason for the steep onset observed for the leaf litter sample in unclear.…”
mentioning
confidence: 86%
“…One of the characteristics of biological INPs is that they include a vast variety of different particle types, ranging 55 from primary biological particles such as bacteria, fungi and pollen to complex organic particles carrying different ice-nucleating agents and originating from biogenic sources (Schnell and Vali, 1973;Hoose and Möhler, 2012;Murray et al, 2012;Augustin et al, 2013;O'Sullivan et al, 2014;Tobo et al, 2014;Conen et al, 2016;Steinke et al, 2016). An example for complex organic particles are agricultural soil dust particles where the observed high ice nucleation efficiency can be linked to microbiological activity and the presence of organic 60 macromolecules (O'Sullivan et al, 2014;Tobo et al, 2014;Hill et al, 2016;Steinke et al, 2016;Suski et al, 2018). The expression of bacterial and fungal ice-active proteins is highly variable, also because environmental stress (e.g.…”
Section: Introductionmentioning
confidence: 99%